The Effect of Interest Rate and Export on Foreign Exchange Reserves in Indonesia - Puspita, Velda; Kurniawan, Mahrus Lutfi Adi (INCOME: Innovation of Economics and Management, 2024)
Good management of foreign exchange reserves during a crisis has the effect of improving the performance of the domestic economy and adding to the welfare gains from optimal management of foreign exchange reserves is reducing the welfare costs of liquidity shocks. Research on exchange reserves should be developed, because it shows the economic power of a country to do more international transactions and face an economic crisis. Foreign exchange reserves were developed using macroeconomic variables such as foreign interest rates, bi rate, exports, and foreign loans with an ordinary least square (OLS) approach. The results of the analysis show that foreign interest rates, exports and foreign loans have a positive influence on foreign exchange reserves, while the domestic interest rate variable has a negative influence on foreign exchange reserves. The government needs to implement policies that are appropriate and appropriate to the situation in order to minimize the reduction in foreign exchange reserves.